2013
DOI: 10.1136/tobaccocontrol-2013-051286
|View full text |Cite
|
Sign up to set email alerts
|

Marketing cigarettes when all else is unavailable: evidence of discounting in price-sensitive neighbourhoods

Abstract: The provision of substantial multi-pack discounts and lower prices in postcodes with a higher proportion of price-sensitive smokers (young people and those from lower socioeconomic groups) is consistent with targeted discounts being used as a tobacco marketing strategy. The results support policy interventions to counter selective discounts and to require disclosure of trade-based discounts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…A systematic audit of tobacco retailers conducted in New South Wales (NSW) (Australia's most populous state) identified, inter alia, retailers who were no longer selling tobacco,17 providing the opportunity to explore which retailers are most likely to stop selling tobacco, and why. Tobacco is widely available in Australia, and is typically sold in supermarkets, tobacconists, convenience stores, petrol stations, newsagents and licensed premises (ie, outlets licensed to sell alcohol).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic audit of tobacco retailers conducted in New South Wales (NSW) (Australia's most populous state) identified, inter alia, retailers who were no longer selling tobacco,17 providing the opportunity to explore which retailers are most likely to stop selling tobacco, and why. Tobacco is widely available in Australia, and is typically sold in supermarkets, tobacconists, convenience stores, petrol stations, newsagents and licensed premises (ie, outlets licensed to sell alcohol).…”
Section: Introductionmentioning
confidence: 99%
“…The finding has particular importance by showing that removal of in-store advertising and point-ofsale promotion, while important, does not fully eliminate retail-related stimuli to smoke. Together with other studies documenting evidence that tobacco companies may manipulate the order of brand listing (Wakefield et al, 2012) and the price of cigarettes (Burton et al, 2014), these results have two implications. First, restricting the number of tobacco outlets, and, second, reducing the prominence of price listings could decrease the triggers to smoke that may undermine quit attempts.…”
Section: Resultsmentioning
confidence: 78%
“…In particular, participants reported that images of a tobacconist and a liquor store prompted thoughts about buying tobacco. An association between tobacconists and smoking is unsurprising, because tobacconists are the second largest retailer group for cigarettes in Australia, after supermarkets (PricewaterhouseCoopers, 2005), and also sell cigarettes at lower prices than other outlet types (Burton et al, 2014). By contrast, liquor stores have only a tiny percentage of the tobacco market share in Australia (PricewaterhouseCoopers, 2005).…”
Section: Retail Related Cuesmentioning
confidence: 92%
See 1 more Smart Citation
“…Burton et al 12 document the extent of price-reducing marketing strategies in Australia, including multi-pack deals and price discounts, concluding that the prevalence of these promotions was greatest in stores in neighbourhoods with more price sensitive consumers—those with higher percentages of young people and with lower socioeconomic status.…”
Section: Effective Interventionsmentioning
confidence: 99%